Pergeseran Makna Perceraian Bagi Perempuan Pada Masyarakat Aceh Barat - Nurlian Nurlian; Rahma Husna Yana; Irma Juraida (Prodi Sosiologi FISIP Universitas Teuku Umar, 2019)
Abstract*Married to be happy. Every human being wants an eternal marriage until the age separates it, but the fact in the community shows the other side, that marriage is not an eternal relationship with a human child. Divorce is an objective thing that happens in the community, in any society and any country. Divorce for women gives rise to a new status in the community. Widowed status gives different meanings to the community and their acceptance. The society provides a negative stigma for women who bear widow status because widows are considered human beings who bring bad things to their families, themselves, others and the social environment to determine marriage. In the Acehnese community at this time, the widow was interpreted positively and her existence was accepted by the community. The shifting of bad meaning for widows in society now occurs because of socio-cultural changes and seeing that the widow is a human being who must be treated as a human being, not a social problem in the community. Shifting the meaning of a widow, giving birth to a positive impact for single men who marry a widow is a common thing that happens in Acehnese society, no longer the status at issue.